2009
DOI: 10.1073/pnas.0904195106
|View full text |Cite|
|
Sign up to set email alerts
|

Chlorine activation indoors and outdoors via surface-mediated reactions of nitrogen oxides with hydrogen chloride

Abstract: Gaseous HCl generated from a variety of sources is ubiquitous in both outdoor and indoor air. Oxides of nitrogen (NO y ) are also globally distributed, because NO formed in combustion processes is oxidized to NO 2 , HNO 3 , N 2 O 5 and a variety of other nitrogen oxides during transport. Deposition of HCl and NO y onto surfaces is commonly regarded as providing permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
182
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(187 citation statements)
references
References 106 publications
5
182
0
Order By: Relevance
“…Attempts to generate ClNO from the reaction of HCl on silica previously exposed to HONO were unsuccessful. 8 Model calculations provide unique insights into the mechanism of ClNO formation. The investigated reactions and corresponding reaction rate constants at 250 K and room temperatures are summarized in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to generate ClNO from the reaction of HCl on silica previously exposed to HONO were unsuccessful. 8 Model calculations provide unique insights into the mechanism of ClNO formation. The investigated reactions and corresponding reaction rate constants at 250 K and room temperatures are summarized in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the calculations elucidate the temperature dependence of the reactions, which is critical because this chemistry may occur in polar regions as well, where very active chemistry and photochemistry involving oxides of nitrogen has been observed. [30][31][32][33] This chemistry potentially contributes to chemistry indoors as well 8 and thus may be of general environmental importance.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study (Molina et al, 1997) investigated the uptake of ClONO 2 (1-10 × 10 −7 Torr) onto aluminum oxide and Pyrex glass in the presence of HCl (1-10 × 10 −6 Torr) at 210-220 K, and suggested that this process is very efficient, with an uptake coefficient of 0.02, which is > 10 times larger than that onto stratospheric sulfuric acid aerosols. In addition, the uptake of N 2 O 5 onto HCldoped sulfuric acid and SiO 2 (Raff et al, 2009) leads to the formation of ClNO 2 , whose photolysis will release Cl atoms and therefore represent a pathway for chlorine activation (Ghosh et al, 2012). Heterogeneous chlorine activation is not included in the modelling work because of the lack of reliable kinetics data.…”
Section: Discussionmentioning
confidence: 99%
“…24a, the peak disappeared on exposure to gas phase HCl. 585 The yields of ClNO 2 increased with water vapor concentration up to the predicted maxima (DClNO 2 /DN 2 O 5 ¼ 1), which was surprising since water was expected to compete with the HCl reaction, forming HNO 3 instead:…”
mentioning
confidence: 99%
“…24b). 585 In addition, ab initio molecular dynamics simulations show that for water lms on surfaces, N 2 O 5 can be stabilized at the air-water interface in such a way that reaction with Cl À via an S N 2 reaction can occur. 588 Baergen et al 242 proposed that similar chemistry could occur in "urban grime" which contains both oxides of nitrogen and chloride ions, as well as a complex mixture of organics.…”
mentioning
confidence: 99%